Contextual Weaning Process for 3–4-Year-Old Playgroup Students - Mochammad Ramli Akbar; Intan Malina (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
This study describes the weaning process for students who are still attached to their parents or caregivers at the start of learning in play groups using contextual learning and describes the factors that influence it. Qualitative descriptive research with the subjects of school principals, teachers, students, and parents in Kemuning Kepanjen playgroup, through the process of observation, interviews, and documentation analysis. The results of the research show that the strategy for weaning students using contextual learning media and infrastructure in a fairly complete learning environment. The chronology of the weaning process is: (1) preparation, (2) weaning process and (3) follow-up. This strategy is supported by quite complete outdoor media, good communication and socialization patterns, participation and support of parents in the environment around the school. The factors that influence the weaning process are (1) early childhood socialization, (2) the initial process of introducing learning to the environment, (3) effective communication patterns between teachers and parents, (4) teacher's strategies during early learning, and (5) media infrastructure that is complete, safe, and easily accessible. There were no significant obstacles in the weaning process, apart from variations in the communication between teachers and parents, and the conditions that were there were interrelated